Multi-representation Analysis of General Chemistry Books on Chemical Bonding Subject - Rizal; Wiji; Tuszie Widhiyanti; Novianti Islahiah (Chemistry Education Department of Education and Teaching Faculty, 2024)
This research is a preliminary study that focuses on multi-representation analysis of the chemical bonding topic in three general chemistry of text books. The analysis was carried out to find out how concepts are explained based on the three levels of chemical representation, especially on ionic and covalent bonding, which are the basis for further research in developing intertextual-based learning strategies. Analysis was carried out at the macroscopic-symbolic and sub microscopic-symbolic levels usingmulti-representation analysis table that was adopted from Gkitzia et al., 201 for three general chemistry books, that are 1) Whitten, K.W, et.al. (2014). Chemistry 10th edition. English: Brooks/Cole Cengage Learning; 2) Chang, R. (2010). Chemistry 10th edition. New York : The McGraw-Hill Companies; and 3) Silberberg, M.S, and Amateis, P.G. (2021). Chemistry: the molecular nature of matter and change 9th edition. New York : The McGraw-Hill Companies. The analysis results show that book: Silberberg, M.S, and Amateis, P.G. (2021). Chemistry: the molecular nature of matter and change 9th edition. New York : The McGraw-Hill Companies has the most complete macroscopic-symbolic and sub microscopic-symbolic representation levels on the four main concept labels of chemical bonding, so that they can become standard reference material in developing chemical representations that will be used in intertextual learning strategies.